Heuristic Supply Chain Optimization of Networked Maintenance Companies. (2015) - Bányai, Tamás; Veres, Péter; Illés, Béla
Abstract: This paper considers the problem of networked maintenance companies and the connected purchasing processes. Today's successful operation of companies views maintenance as a high priority to ensure maximum utilisation of resources. In this article, a mathematical model is first developed to formulate the problem of finding the optimal make-or-buy solution for complex spare part production. The model seeks the optimal proportion of in-house and outsourced productions, as well as the order quantity so as to minimize the total costs while taking into account order limits. Next, we demonstrate an enhanced harmony search algorithm dealing with multi-objective supply chain model to find the optimum make-or-buy solution of a given maintenance related supply chain problem. We also discuss the sensibility analysis of the heuristic optimisation method and propose optimal process parameters for a high convergence. Numerical results demonstrate how the proposed model supports the make-or-buy decision and helps to reduce the total costs while keeping high availability to fulfil maintenance tasks.